Ludwig Senfl,Motets for Five Voices: New Senfl Edition 3 - Gasch, Stefan (Verlag der Österreichischen Akademie der Wissenschaften, 2022)
The third volume of the Neue Senfl Edition (NSE) publishes all five-part motets for the first time. In addition to well-known motets such as Ave, Rosa sine spinis or the five-part version of Senfl's Nisi Dominus, it also contains numerous first editions (such as the monumental Te Deum) and provides valuable insights into Senfl's handling of the tradition of combining several texts in one composition. The critical reports accompanying the edition provide information about the texts, the chorale models, the evaluation of the sources (including a synoptic presentation of the readings) as well as the work-historical context of each motet.